Elaboración de una bebida fermentada no láctea a base de leche de soya Glycine Max L - Mariño Gavilanez, Carmen Alejandra (2024)
A non-dairy fermented soybean-based beverage was made with the Cornell extraction technique to obtain milk from the soybean, which improved the flavor, the process of making the drink was carried out similar to that of a yogurt using Lactobacillus bulgaricus and Streptococcus thermophilus in an incubation time of 8 hours. The experimental design used was a 3x2 factorial design. A randomized complete block design was used in which a sensory evaluation of 6 treatments was carried out in terms of the two independent variables selected based on the organoleptic characteristics experienced, such as flavors and type of sweeteners, composed of a sensory panel of 30 untrained people, the same ones who chose the best sample. The characterization of the physicochemical properties resulted in 0.85% titratable acidity with pH of 4.20, 14º Brix, density of 0.15gr/ml. For the microbiological analyses, the best T1 treatment was used based on the sensory analysis that was performed on 30 untrained panelists, visually showing <10 CFU in the Petri film.